Coupling of Carbon Dioxide with Epoxides Efficiently Catalyzed by Thioether‐Triphenolate Bimetallic Iron(III) Complexes: Catalyst Structure–Reactivity Relationship and Mechanistic DFT Study. Issue 20 (25th August 2016) - Della Monica, Francesco; Vummaleti, Sai V. C.; Buonerba, Antonio; Nisi, Assunta De; Monari, Magda; Milione, Stefano; Grassi, Alfonso; Cavallo, Luigi; Capacchione, Carmine
Abstract: A series of dinuclear iron(III) I complexes supported by thioether‐triphenolate ligands have been prepared to attain highly Lewis acidic catalysts. In combination with tetrabutylammonium bromide (TBAB) they are highly active catalysts in the synthesis of cyclic organic carbonates through the coupling of carbon dioxide to epoxides with the highest initial turnover frequencies reported to date for the conversion of propylene oxide to propylene carbonate for iron‐based catalysts (5200 h −1 ; 120 °C, 2 MPa, 1 h). In particular, these complexes are shown to be highly selective catalysts for the coupling of carbon dioxide to internal oxiranes affording the corresponding cyclic carbonates in good yield and with retention of the initial stereochemical configuration. A density functional theory (DFT) investigation provides a rational for the relative high activity found for these Fe(III) complexes, showing the fundamental role of the hemilabile sulfur atom in the ligand skeleton to promote reactivity. Notably, in spite of the dinuclear nature of the catalyst precursor only one metal center is involved in the catalytic cycle. Abstract :